The Establishment Of Embryogenic Callus Culture Of Hyoscyamus Niger And The Detection Of Hyoscyamine In The Culture [SB118.46. N576 2008 f rb]. - Nhawal Aminie Saidon, Nhawal Aminie Saidon (2008)
Embryogenic callus of Hyoscyamus niger could be induced from the leaf, petiole and root explants however the best embryogenic callus induction was obtained from the leaf explants cultured on MS medium supplemented with 6.0 mg/L picloram after four weeks of culture.